On Jones’ index for real W*-algebras - Albeverio, Sergio; Ayupov, Shavkat; Dadakhodjaev, Rashithon; Rakhimov, Abdugafur (Eurasian Mathematical Journal, 2010)
The notions of the real coupling constant and the index for real W* -algebras are introduced and investigated. The main tool in our approach is the reduction of real W* -algebras to involutive *-anti-automorphisms of their complex enveloping von Neumann algebras. Similar to the complex case the values of the index for type II1 real factors are calculated.